Pengaruh Pelayanan, Harga, Kemasan, Inovasi Dan Kekuatan Merek Terhadap Kepuasan Konsumen RM. Gudeg Adem Ayem di Solo - Muldiantoro, Yudha Anggun Setyo, Sri Murwanti, S.E., M.M (2015)
The purpose of this research is to know the influence and variables simultaneously partial evaluation service , the price of , packaging , innovation and strength brand give the effect on customer satisfaction RM Gudeg Adem Ayem in Solo The research is descriptive quantitative research uses a questionnaire as a means of data collection software analyzed using data for windows version of sports spss 22 .Was conducted using non-probability sample the determination of the sampling method of accidental through a method of sampling , with the number of respondents be used is 100 respondents. Hasil penelitian didapat baik secara bersama-sama maupun secara sendiri-sendiri variabel pelayanan, harga, kemasan, inovasi dan kekuatan merek memberikan pengaruh terhadap kepuasan konsumen. Dari hasil penelitian diketahui bahwa variabel inovasi merupakan variabel yang memberikan pengaruh paling besar terhadap kepuasan konsumen. Key Words : Service, Price, Pakcing, Inovatiob, Strenght of Brand and Customer Satisfaction